Tantangan Penelitian Teks Sastra-Interpretasi dan Kritik Teks - Dami N Toda (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2006)
The dominance of the Western literary theory in Indonesia hasl resulted in growing wilderness of literary theories. It has even resulted in the glorification of certain literary theory as if there is no other literary theory worth studying. This reality has caused Subagio Sastrowardoyo to develop a concept: “If we are honest with ourselves, we have to admit that the deeper we go into the jungle of crisscrossing thoughts in modern Western literary theory, the more difficult it is for us to have a firm hold of the truth in literary criticism.” In other words, Subagio Sastrowardoyo is reminding Indonesia literary critics not to be trapped in a theoretical crisis that will distance themselves from the practice od literary criticism.The basic question of this article is whetger literary theory is considered literary criticisim or literary interpretation. To answer this question two factors will be oserverd, namely 1) literary truth or textual theory truth; 2) literary truth should be the source for literary theory deductions. Comprehending these two factors basically challenge academicians, specifically literary researchers, to closely observe the basics when performing literary criticism while applying literary theories with its own differing perspective.